ANALISIS SWOT SEBAGAI STRATEGI PENGEMBANGAN IKIP PGRI SEMARANG1 - MARYADI . (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2014)
AbstractIn it age of ?óÔé¼?ª / fourty five years old, IKIP PGRI Semarang has been challenging to solve various problems internally and externally, it is challenged to the develop the quality of the humand resourses as this dozen of IKIP PGRI Semarang have been Profesors, Doctors, and magisters and management, to raise fund and building. Externally, it is challenged to respond to the globalization, development of technology and information system. Development of relations to university Malaysia, relations to teacher?óÔé¼Ôäós Brunei Darusalam and soon.Based on the internal and external condition, IKIP PGRI Semarang has opportunities and the same time challengers. In order to understand and to respond to the these all things it is necessary to analyze them by SWOT, by which the weaknesses and challengers internally and externally can be solved smoothly, and the same time can develop its strength and opportunities to be able to achieve the good of founding IKIP PGRI Semarang. Therefore, SWOT can be used a strategy to develop and achieve the goal of the founding of IKIP PGRI Semarang.Furthermore, to anticipate and to solve the problems and challengers of the IKIP PGRI Semarang it has been founded and development strategy program. This program purposes to respond the challengers and to provite the need of the society nowadays and future. The strategy is consisted of ten affairs, namely institutional, management, human resouses, curriculum library, research, community development, students affair, building, the cooperation with other institution affair, building, the cooperation with other institution in Indonesia and Foreigner).Key Words: Analyze, SWOT, DevelopmentAbstrakMenginjak empat puluh lima tahun, IKIP PGRI Semarang telah menantang untuk memecahkan berbagai masalah internal dan eksternal, ia ditantang untuk mengembangkan kualitas SDM. Secara eksternal, ia ditantang untuk merespon globalisasi, perkembangan Brunei Darusalam dan segera lainnya .Berdasarkan kondisi internal dan eksternal, IKIP PGRI Semarang memiliki peluang dan penantang waktu yang sama. Dalam rangka untuk memahami dan merespon ini perlu dilakukan analisis SWOT. SWOT digunakan sebagai strategi untuk mengembangkan dan mencapai tujuan berdirinya IKIP PGRI Semarang .Selain itu, untuk mengantisipasi dan memecahkan masalah dan penantang dari IKIP PGRI Semarang itu telah didirikan program strategi pembangunan. Tujuan program ini untuk merespon penantang dan kebutuhan masyarakat saat ini dan masa depan. Strategi ini terdiri dari sepuluh hal, yaitu kelembagaan, manajemen, SDM , perpustakaan kurikulum, penelitian,1 Hasil Penelitian Tahun ?2 Dosen PPs (S-2) Universitas PGRI Semarangpengembangan masyarakat, mahasiswa, bangunan, kerjasama dengan institusi lain di Indonesia dan luar negeri.Kata kunci: Analisis , SWOT , Pembangunan